The Impact of Organizational Justice on Employee Retention: Evidence from Oman - Imran, Rabia; Allil, Kamaal (International Review of Management and Marketing, 2016)
Increasingly, retaining competent employees is becoming a major concern for organizations. Sustainability and success of organizations are dependent on reducing turnover. Therefore, this research is designed to identify the role played by organizational justice dimensions in retaining employees within organizations. For that, a sample of 148 respondents working in Omani airports was selected for the study. The results reveal that all three dimensions of organizational justice i.e. distributive, procedural and interactional justices have positive and significant impact on employee retention. Implications and directions for future research were also discussed. Keywords: Employee Retention; Distributive Justice; Procedural Justice; Interactional Justice. JEL Classifications: G2, J28